Lipidomics of Huntington’s Disease: A Comprehensive Review of Current Status and Future Directions - Ali Yilmaz; Sumeyya Akyol; Nadia Ashrafi; Nazia Saiyed; Onur Turkoglu; Stewart F. Graham (Metabolites)
Background: Huntington’s disease (HD) is a multifaceted neurological disorder characterized by the progressive deterioration of motor, cognitive, and psychiatric functions. Despite a limited understanding of its pathogenesis, research has implicated abnormal trinucleotide cytosine-adenine-guanine CAG repeat expansion in the huntingtin gene (HTT) as a critical factor. The development of innovative strategies is imperative for the early detection of predictive biomarkers, enabling timely intervention and mitigating irreversible cellular damage. Lipidomics, a comprehensive analytical approach, has emerged as an indispensable tool for systematically characterizing lipid profiles and elucidating their role in disease pathology. Method: A MedLine search was performed to identify studies that use lipidomics for the characterization of HD. Search terms included “Huntington disease”; “lipidomics”; “biomarker discovery”; “NMR”; and “Mass spectrometry”. Results: This review highlights the significance of lipidomics in HD diagnosis and treatment, exploring changes in brain lipids and their functions. Recent breakthroughs in analytical techniques, particularly mass spectrometry and NMR spectroscopy, have revolutionized brain lipidomics research, enabling researchers to gain deeper insights into the complex lipidome of the brain. Conclusions: A comprehensive understanding of the broad spectrum of lipidomics alterations in HD is vital for precise diagnostic evaluation and effective disease management. The integration of lipidomics with artificial intelligence and interdisciplinary collaboration holds promise for addressing the clinical variability of HD.